Ücretsiz mevsimsel grip aşılarını yaptıran kişilerin, ücretsiz pandemik grip aşısı karşısındaki tutum ve davranışları - Muzaffer Eskiocak; A.Önder Porsuk (Turkish Society of Public Health Specialists, 2011)
Amaç: Bu çalışma, mevsimsel grip aşısına (MGA) ücretsiz erişen insanların tutum ve davranışlarını, yine ücretsiz, ama çeşitli tartışmalara konu olan pandemik grip aşısı (PGA) karşısındaki tutum ve davranışlarıyla karşılaştırmak amacıyla yapılmıştır. Yöntem: Araştırma tanımlayıcı tipte bir araştırmadır ve Kırklareli-Evrensekiz Sağlık Ocağı bölgesinde, Şubat,2009-Şubat,2010 tarihleri arasında yürütülmüştür. Çalışma anketi yüz-yüze görüşme yöntemiyle doldurulmuştur. Bulgular: Katılımcıların %99,2'si (n=125) kamu kurumlarının ücretsiz MGA sağlamasını destekliyordu ve tamamı (N=126) gelecek yıl da ücretsiz MGA temin edilmesini istiyordu. 2010 yılında yapılan ikinci ankette ücretsiz sağlanan PGA olanların oranının ise %4 (n=5) olduğu tespit edildi. Sonuç: Bağışıklama hizmetlerinden yararlanmada ekonomik faktörlerin çok önemli olduğu, ancak toplumun güven duygusunun zedelenmesinin, ücretsiz sağlansa da aşılamayı ciddi düzeyde engellediği saptanmıştır. Anahtar Kelimeler: Mevsimsel grip aşısı, pandemik grip aşısı  Attitudes and behaviors related to free pandemic influenza vaccination of who gets vaccinated with free seasonal influenza vaccine  Objective: This study aims to compare attitudes and behaviors of the people who receive free Seasonal Influenza Vaccine (SIV) with their attitudes and behaviors against Pandemic Influenza Vaccine (PIV) which is also free, but controversial. Method: This study is a descriptive survey which was carried out within the service area of Evrensekiz Primary Healthcare Center (PHC) in Kırklareli province and it was conducted between February 2009 and February 2010. The questionnaire has been applied by face to face interviews. Results: 99,2%of participants (n=125) supported providing free influenza vaccine by governmental organizations and all of them (N=126) wanted to get free influenza vaccine the next year. In the second questionnaire run in 2010, it was determined that only 4%of the participants accepted free PIV. Conclusion: It has been determined that economic factors were highly important in benefiting from immunization services, however, that vaccination services were impeded seriously by the damage in people's sense of trust, even the services are free Key Words: Seasonal Influenza Vaccine, Pandemic Influenza Vaccine